L’itinéraire d’Adelbert von Chamisso : de l’hybride à l’universel - Vera Gandelman-Terekhov (Recherches Germaniques)
This article explores the notion of hybridity which applies both to Chamisso’s unique destiny, at the crossroads of French and German culture, and to his unclassifiable work Peter Schlemihls wundersame Geschichte (1814). The character’s inadequacy reflects the situation of the author torn between two countries. Lack generates movement and the search for otherness, leading to a genuine universal. The journeys undertaken by the fictional character and Chamisso himself (his expedition on the Russian ship Rurik, 1815-1818) find their literary expression in Gedichte (1831) and Reise um die Welt (1836). These writings reveal the extent of his knowledge of distant, exotic worlds. These poems show Chamisso’s ability to evoke the history of foreign countries and to transpose poems from other languages into German. They are not exactly translations, but poetic transpositions, and, thus, autonomous works, as his versions of French poems into German attest. Thanks to this quest the author manages to reconcile his French origins, remembered in Das Schloß Boncourt, and his German cultural identity.